Component composition of polyphenolic compounds in inflorescences of Tagetes erecta L. var. "Antigua F 1 Orange" - Mazulin, O. V.; Fukleva, L. A.; Voytenko, T.; Saliy, O.; Mazulin, G. V.; Мазулін, Олександр Владиленович; Фуклева, Лариса Анатоліївна; Войтенко, Т.; Салій, О.; Мазулін, Георгій Владиленович (My University, 2025)
Aim of study is determination of the component composition and quantitative content of polyphenolic compounds in the inflorescences of Tagetes erecta L. var. “Antigua F 1 Orange”. Material and methods. The plant material consisted of air-dried inflorescences of Tagetes erecta L. cultivated in Ukraine, variety var. “Antigua F1 Orange”, collected during the flowering period (June – September 2023–2024). The component composition and quantitative content of polyphenolic compounds were determined using thin-layer chromatography (TLC) on glass-backed plates “Merkieselguhr F254” 20 x 20 (Merck KGaA, Germany) with the densitometer device “Biostep” CD 60 (Germany) and highperformance liquid chromatography (HPLC) “Shimadzu LC-20” with a UV detector (Japan). Standard compound samples were sourced from “Supelco Analytical, Sigma-Aldrich” (USA). Research results. In the inflorescences of Tagetes erecta L. var. “Antigua F1 Orange”, the quantitative composition of 22 primary polyphenolic compounds was identified and analyzed. Among these, 13 were classified as flavonoids, while 9 were categorized as hydroxycinnamic acids. The quantitative flavonoid contents were 20,40 ± 2,14 and hydroxycinnamic acids 5,60 ± 0,64% respectively. Мета дослідження – визначення компонентного складу та кількісного вмісту поліфенольних сполук у суцвіттях Tagetes erecta L. var. “Antigua F 1 Orange”. Матеріал і методи. Рослинною сировиною були повітряно-сухі суцвіття Tagetes erecta, культивованого в Україні сорту “Antigua F 1 Orange” під час цвітіння (червень – вересень 2023–2024 років). Компонентний склад і кількісний вміст поліфенольних сполук визначали методом ТШХ, на пластинах зі скляною підкладкою “Merkieselguhr F254” 20 х 20 (Merck KGaA, Німеччина), на денситометрі “Biostep” CD 60 (Німеччина) та ВЕРХ “Shimadzu LC-20” з УФ-детектором (Японія). Використано стандартні зразки сполук фірми “Supelko Analytical, Sigma-Aldrich” (USA). Результати дослідження. У суцвіттях чорнобривців прямостоячих Tagetes erecta L. сорту “Antigua F 1 Orange” ідентифіковано та встановлено кількісний вміст до 22 основних поліфенольних сполук. З них 13 віднесені до флавоноїдів і 9 до гідроксикоричних кислот. Кількісний вміст суми флавоноїдів – до 20,40 ± 2,14, гідроксикоричних кислот – 5,60 ± 0,64%.
Компонентний склад поліфенольних сполук суцвіть Tagetes erecta L. var. “Antigua F1 Orange”
Keywords: marigold; Tagetes erecta L. var. “Antigua F1 Orange”; thin layer chromatography; High-Performance Liquid chromatography; qualitative and quantitative analysis; flavonoids; hydroxycinnamic acids; чорнобривці; Tagetes erecta L. сорту “Antigua F 1 Orange”; ТШХ; ВЕРХ; якісний і кількісний аналіз; флавоноїди; гідроксикоричні кислоти